PENGARUH CINTA UANG, KEPUASAN GAJI DAN INTEGRITAS TERHADAP KORUPSI POLISI - Denny Hariyanto; Novi Hidayat; Rismawati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Corruption is a serious crime that has widespread impacts on social welfare, economic development, and public trust. Ironically, corrupt practices are also found within police institutions, which are responsible for law enforcement and anti-corruption efforts. This study aimed to examine the influence of love of money, salary satisfaction, and integrity on corruption tendencies among police officers. A quantitative survey design was employed in this research. Data were collected using questionnaires consisting of four measurement scales from 222 police officers serving at the East Jakarta Police Resort, Indonesia. Multiple regression analysis was applied to determine the effects of the independent variables on corruption tendencies. The findings revealed that love of money and integrity significantly influenced corruption tendencies among police officers, whereas salary satisfaction had no significant effect. In addition, the results indicated that 51% of respondents were classified as having a high potential for corruption. These findings suggest that psychological factors, particularly excessive attachment to money and low integrity, play a more substantial role in explaining corruption tendencies than salary satisfaction. The study highlights the importance of strengthening integrity and ethical values as key strategies for preventing corruption within police institutions. These findings suggest that psychological and moral factors, particularly love of money and integrity, play a more substantial role in predicting corruption tendencies among police officers than salary satisfaction. Strengthening integrity-based interventions may therefore be an effective strategy for corruption prevention within law enforcement institutions. ABSTRAK Korupsi merupakan salah satu kejahatan yang berdampak luas terhadap kehidupan sosial, ekonomi, dan pembangunan suatu negara. Ironisnya, praktik korupsi juga ditemukan pada institusi kepolisian yang memiliki tugas utama dalam penegakan hukum dan pemberantasan korupsi. Penelitian ini bertujuan untuk menganalisis pengaruh cinta uang (love of money), kepuasan gaji, dan integritas terhadap kecenderungan perilaku korupsi pada anggota kepolisian. Penelitian menggunakan pendekatan kuantitatif dengan desain survei. Data dikumpulkan melalui kuesioner yang terdiri atas empat skala pengukuran dan melibatkan 222 anggota Kepolisian Resort Jakarta Timur, DKI Jakarta, sebagai responden. Data dianalisis menggunakan teknik regresi berganda untuk menguji pengaruh masing-masing variabel independen terhadap korupsi. Hasil penelitian menunjukkan bahwa cinta uang dan integritas berpengaruh signifikan terhadap kecenderungan korupsi pada anggota kepolisian, sedangkan kepuasan gaji tidak terbukti berpengaruh signifikan. Temuan penelitian juga menunjukkan bahwa sebanyak 51% responden berada pada kategori potensi korupsi yang tinggi. Dengan demikian, faktor psikologis berupa kecintaan yang berlebihan terhadap uang serta rendahnya integritas menjadi faktor yang lebih dominan dalam menjelaskan kecenderungan korupsi dibandingkan faktor kepuasan gaji. Penelitian ini menegaskan pentingnya penguatan integritas dan pembinaan nilai-nilai etika sebagai strategi pencegahan korupsi di lingkungan kepolisian.